2009
DOI: 10.1161/strokeaha.108.529958
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Tract Pre-Wallerian Degeneration

Abstract: Background and Purpose-In neonatal arterial ischemic stroke, pre-Wallerian degeneration in descending corticospinal tracts (DCST) on diffusion MRI (DWI) predicts poor outcome. This signal has not been studied in older children. Methods-A consecutive arterial ischemic stroke cohort (1 month to 18 years) with acute DWI and Ͼ12 months of follow-up were enrolled (SickKids Children's Stroke Program). DCST-DWI variables were quantified with a validated software technique and correlations to the Pediatric Stroke Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 29 publications
5
35
0
Order By: Relevance
“…Univariate analyses failed to detect any differences. These results, obtained at the acute stage, are in line with previous studies carried out at the subacute or chronic phases [3,2,4]. Our results suggest that spatially regularized SVM might be useful to analyze MR images acquired in clinical routine as soon as 24 hours post stroke onset.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Univariate analyses failed to detect any differences. These results, obtained at the acute stage, are in line with previous studies carried out at the subacute or chronic phases [3,2,4]. Our results suggest that spatially regularized SVM might be useful to analyze MR images acquired in clinical routine as soon as 24 hours post stroke onset.…”
Section: Resultssupporting
confidence: 91%
“…The location of the lesions has been suggested to represent a better predictor than their global volume [2]. At the subacute or chronic phases, previous studies have shown that damages to the corticospinal tract (CST) [3] and lesions to the primary sensorimotor cortex [2,4] correlated with poor motor outcome. At the acute stage, regional changes in the apparent diffusion coefficients (ADC) were suggested as early quantitative indices of regional irreversible ischemic damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on diffusion-weighted imaging in term born infants with arterial stroke showed that visually detected abnormalities in signal intensity at the level of the PLIC and cerebral peduncle are suggestive of pre-Wallerian degeneration. They were noted to be predictive of subsequent Wallerian degeneration and an adverse motor outcome (14,18,19). The present study adds that changes in FA after PVHI can already be visually detected at a very early age.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that asymmetries in FA of the CST after PVHI and arterial stroke at TEA indicate CST injury that is associated with the development of USCP (14)(15)(16). The present study adds that in preterm infants with a PVHI, asymmetry in FA can be detected within weeks after the onset of PVHI reflecting early alterations in CST integrity that relate to later motor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, function-specific imaging biomarkers may have greater potential to predict outcomes. The leading example is early diffusion imaging changes in the descending corticospinal tract, which appear to correlate well with motor outcome in neonatal (e.g., cerebral palsy), childhood, and adult stroke (12,13). We have shown recently, using MRI in a neonatal model of hypoxia-ischemia, that similar to changes in the descending corticospinal tract in human infants, there are acute (by 24 h) increases in T 2 and decreases in the apparent diffusion coefficient (ADC) of water, consistent with early Wallerian degeneration (14).…”
mentioning
confidence: 99%